Luaran Klinis dan Efektivitas Biaya Ceftazidim-Avibactam Pada Terapi Pneumonia Terkait Ventilator - Ayunda Nur Hidayatiningsih; Nanang Munif Yasin; Tri Murti Andayani (Fakultas Farmasi Universitas Setia Budi, 2026)
A high rate of morbidity, mortality, and medical expenses has been observed in cases of ventilator-associated pneumonia (VAP), particularly when it is associated with carbapenem-resistant Enterobacteriaceae (CRE). Conventional medicines such as meropenem and colistin have been the standard of care. However, there is growing interest in ceftazidime-avibactam (CAZ-AVI) as a potential alternative. This review aims to evaluate the clinical outcomes and economic implications of CAZ-AVI in the management of VAP. A literature search was conducted across PubMed, ScienceDirect, Google Scholar, and Scopus from 2015 until July 2025. Studies were included if they reported clinical outcomes and cost-effectiveness of CAZ-AVI in patients with VAP. Data were extracted regarding interventions, comparators, outcomes, and economic evaluations. Seven studies met the inclusion criteria. The administration of CAZ-AVI has been demonstrated to be associated with enhanced clinical outcomes, including a reduction in mortality and nephrotoxicity, particularly when compared to colistin-based regimens. Economic evaluations consistently showed that CAZ-AVI was cost-effective, with ICERs ranging from 3,317 to 35,328 per QALY, depending on country-specific thresholds. CAZ-AVI has shown positive clinical results and is a cost-effective treatment for VAP, especially in cases of CRE infections.